Intravenous paracetamol and intraocular pressure reduction: mannitol may also be involved - Allegaert K (Dove Medical Press, 2016)
Karel Allegaert1,2 1Intensive Care, Department of Surgery, Erasmus MC Sophia Children’s Hospital, Rotterdam, the Netherlands; 2Department of Development and Regeneration, KU Leuven, BelgiumI read, with great interest, the paper on the intraocular pressure-lowering properties of intravenous paracetamol (acetaminophen) recently published in this journal by van den Heever and Meyer.1 The authors documented a decrease from baseline in mean intraocular pressure of 15.7% in a 6-hour time interval following intravenous paracetamol (1 g Perfalgan®, Bristol-Myers Squibb, New York, NY, USA) administration. This mean decrease was moderate but relevant when compared to, for example, topical timolol (–25.3%, single drop 0.5% timolol maleate) or oral acetazolamide (–23.1%, 250 mg). Although the authors provided potential relevant mechanistic arguments in support of a link between paracetamol administration and intraocular pressure through the endocannabinoid system, we would like to draw attention to the fact that – when intravenous paracetamol is administered – a relevant amount of mannitol is coadministered.View the original paper by van den Heever and Meyer